Effect of subchronic oral administration of glucosamine in the regulation of body weight, glycemia and dyslipidemia induced hypercholesterolemic Wistar rat - BARRIENTOS ALVARADO, Cornelio; SÁNCHEZ VÁZQUEZ, Jorge; Silvia CÁRDENAS OSCOY, María Atanasia; GARRIDO ACOSTA, Osvaldo; ANGUIANO ROBLEDO, Liliana (Revista de Nutrição, 2014)
Objective This study evaluated the effect of oral glucosamine on overweight and dyslipidemia caused by a high-fat diet in rats. Methods our groups of Wistar rats: fed with commercial rodent food and drinking water without (control group) and with glucosamine (500 mg kg-1 per day) and a high-fat diet enriched with 24% (g/g) butter pork and drinking water without and with glucosamine, for 22 weeks; the body weight, abdominal fat, blood glucose, triglycerides, total cholesterol, and high density lipoprotein in serum were evaluated. Results Body weight gain, increased blood glucose levels and dyslipidemia were observed in the high-fat diet group versus the control group (p<0.001). When glucosamine was administered the same diet the effects were minimized, with a decrease in the amount of abdominal-fat and lipid profile levels in serum (p>0.05), regulated body weight, and high density lipoprotein and glycaemia (p<0.05). The glucosamine did not affect body weight and lipid metabolism in rats when administered with a normal diet. Conclusions Glucosamine regulated the body weight blood glucose and dyslipidemia caused by a high-fat diet, favoring increased high density lipoprotein cholesterol in rats. It did not affect body weight and lipid metabolism when administered with commercial food.